A The Impact of Interprofessional Collaboration on Emergency Referral Decisions for Chronically Ill Patients: The Impact of Interprofessional Collaboration on Emergency Referral Decisions for Chronically Ill Patients - RAMBEY, HARRIS (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
The Impact of Interprofessional Collaboration on Emergency Referral Decisions for Chronically Ill Patients